2014
DOI: 10.1016/j.icarus.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Orbit and bulk density of the OSIRIS-REx target Asteroid (101955) Bennu

Abstract: a b s t r a c tThe target asteroid of the OSIRIS-REx asteroid sample return mission, (101955) Bennu (formerly 1999 RQ 36 ), is a half-kilometer near-Earth asteroid with an extraordinarily well constrained orbit. An extensive data set of optical astrometry from 1999 to 2013 and high-quality radar delay measurements to Bennu in 1999Bennu in , 2005, and 2011 reveal the action of the Yarkovsky effect, with a mean semimajor axis drift rate da=dt ¼ ðÀ19:0 AE 0:1Þ Â 10 À4 au=Myr or 284 AE 1:5 m=year. The accuracy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
208
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 215 publications
(218 citation statements)
references
References 52 publications
10
208
0
Order By: Relevance
“…These densities are not, a priori, unreasonable estimates for Bennu. Chesley et al (2013), obtain an estimate of the bulk density of the entire asteroid to be ~ 1 g cm -3 from a measurement of the Yarkovsky effect on the orbit of Bennu, suggesting a fairly uniform porosity of about 0.5 for the entire asteroid, though the uncertainties are large enough to prevent drawing any firm conclusions. More recent studies of the densities of L-chondrites (Consolmagno, Britt and Mackey, 2008) give slightly lower densities (by 5-10%), and the results should scale with that value.…”
Section: Near-surface Bulk Densitymentioning
confidence: 98%
See 1 more Smart Citation
“…These densities are not, a priori, unreasonable estimates for Bennu. Chesley et al (2013), obtain an estimate of the bulk density of the entire asteroid to be ~ 1 g cm -3 from a measurement of the Yarkovsky effect on the orbit of Bennu, suggesting a fairly uniform porosity of about 0.5 for the entire asteroid, though the uncertainties are large enough to prevent drawing any firm conclusions. More recent studies of the densities of L-chondrites (Consolmagno, Britt and Mackey, 2008) give slightly lower densities (by 5-10%), and the results should scale with that value.…”
Section: Near-surface Bulk Densitymentioning
confidence: 98%
“…Further radar observations obtained in September 2011 had too low a signal-to-noise ratio (SNR) to be useful for characterizing the shape of the asteroid. Chesley et al (2013) used them, along with the other observations reported here, for computing its orbit. The observations at Goldstone have lower (by a factor of about 20) SNR than the Arecibo images, but many were obtained at times when the object was not visible from Arecibo.…”
Section: Observationsmentioning
confidence: 99%
“…APPENDIX A: PHYSICAL PARAMETERS OF ASTEROID (101955) BENNU Table 6 summarizes the relevant physical parameters for Bennu [30]. Surface emissivity: 0.90 ± 0.05…”
Section: Acknowledgementmentioning
confidence: 99%
“…In particular, the Yarkovsky effect could explain the transportation of asteroids from the main belt region to the inner solar system (Bottke et al 2006). It also becomes necessary for accurate orbit determination or prediction of trajectory of near-Earth asteroids (NEA), in particular, in the context of close approach or impact predictions (Farnocchia et al 2013a;Chesley et al 2014). …”
Section: Introductionmentioning
confidence: 99%